2019
DOI: 10.1021/acs.jpcb.9b03757
|View full text |Cite|
|
Sign up to set email alerts
|

Trade-Offs between Error, Speed, Noise, and Energy Dissipation in Biological Processes with Proofreading

Abstract: High accuracy of major biological processes relies on the ability of the participating enzymatic molecules to preferentially select the correct substrate from a pool of chemically similar substrates by activating the so-called proofreading mechanisms. While the importance of such mechanisms is widely accepted, it is still unclear how evolution has optimized the biological systems with respect to certain characteristic properties. Here, using a discrete-state stochastic framework with a first-passage analysis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(69 citation statements)
references
References 37 publications
2
64
0
Order By: Relevance
“…Our examination of the biochemical network for aa-tRNA selection in the E. Coli ribosome 18,21,24,29,30 demostrates that our invariance statement holds in the presence of energy-dissipating cycles on the network. We show that both the error fraction and the normalized energy dissipation can be expressed as flux ratios, and therefore, they are invariant to changes in the energies of the intermediate states on the underlying free-energy landscape.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…Our examination of the biochemical network for aa-tRNA selection in the E. Coli ribosome 18,21,24,29,30 demostrates that our invariance statement holds in the presence of energy-dissipating cycles on the network. We show that both the error fraction and the normalized energy dissipation can be expressed as flux ratios, and therefore, they are invariant to changes in the energies of the intermediate states on the underlying free-energy landscape.…”
Section: Discussionmentioning
confidence: 63%
“…The kinetic parameters (rate constants) that correspond to the various reactions on the corresponding biochemical networks are given in the SI Tabs. S1-S3 23,26,[29][30][31][32] . For simplicity of the notation, we drop all of the prime and ω superscripts on the perturbed steady-state fluxes.…”
Section: Illustrative Examplesmentioning
confidence: 99%
See 1 more Smart Citation
“…where ∆µ = ∆µ KPR for proofreading cycles (N = 3) or ∆µ p for production cycle (N = p) and chemical potentials are hereafter measured in k B T units. We take the approximate physiological values of the chemical potential differences, ∆µ p ∼ 26k B T for poly-peptide elongation, ∆µ p ∼ 11k B T for nucleotide ligation and ∆µ KPR ∼ 20k B T for the hydrolysis KPR step in both systems [40]. For convenience, we also define discrimination factors f i which relate the R and rate constants as f…”
Section: Kinetic Proofreading Circuitsmentioning
confidence: 99%
“…Taking the physiological state as a reference point, they investigated the speed-accuracy trade-off as a function of the kinetic rates, finding that speed is prioritized over error rate. In a follow-up work on the same systems, they found that speed is also prioritized over energy dissipation and output noise [40].…”
Section: Introductionmentioning
confidence: 98%